2015
DOI: 10.1515/amm-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Cast Ni-Cr-Al-C Alloy

Abstract: Nickel based alloys, especially nickel based superalloys have gained the advantage over other alloys in the field of high temperature applications, and thus become irreplaceable at high temperature creep and aggressive corrosion environments, such as jet engines and steam turbines. However, the wear resistance of these alloys is insufficient at high temperatures. This work describes a microstructure of a new cast alloy. The microstructure consists of γ matrix strengthened by γ' fine precipitates (dendrites) im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Recent studies have indicated that the high-temperature mechanical strength and hardness of Ni 3 Al alloys can be significantly improved by the addition of hard-particle reinforcements [11][12][13]. When present in iron, cobalt, and nickel matrices, chromium carbide exhibits high hot-hardness and excellent hightemperature oxidation resistance combined with good wetting ability [14][15]. Hence, chromium carbides are chosen frequently as hard-particle reinforcements for addition into Ni 3 Al-based matrices, to form Cr 3 C 2 /Ni 3 Al composites [8,16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that the high-temperature mechanical strength and hardness of Ni 3 Al alloys can be significantly improved by the addition of hard-particle reinforcements [11][12][13]. When present in iron, cobalt, and nickel matrices, chromium carbide exhibits high hot-hardness and excellent hightemperature oxidation resistance combined with good wetting ability [14][15]. Hence, chromium carbides are chosen frequently as hard-particle reinforcements for addition into Ni 3 Al-based matrices, to form Cr 3 C 2 /Ni 3 Al composites [8,16].…”
Section: Introductionmentioning
confidence: 99%
“…The ASM Alloy Phase Diagram Center database also includes a ternary phase diagram for the Al-Ni-Cr alloy system, which shows the phase relationships among the three main constituents at various temperatures and compositions [4]. This phase diagram exhibits a eutectic reaction at 1410°C and a composition of 54.5% Al, 33.5% Ni, and 12% Cr, where liquid and solid phases coexist.…”
Section: B Ternary Phase Diagrammentioning
confidence: 99%
“…It is commonly used in applications such as aerospace and power generation, where it is subjected to extreme environments and high mechanical stresses. Overall, Al-Ni-Cr alloys are a versatile and widely-used type of alloy that offers a combination of high strength, corrosion resistance [4], and good thermal and electrical conductivity. These properties make them an ideal material for a range of applications in a variety of industries.…”
Section: Introductionmentioning
confidence: 99%
“…However, the wear resistance of monolithic Ni 3 Al intermetallic compounds is usually inadequate under the most extreme conditions of severe sliding, impact wear, and abrasive wear [7,8]. Early studies have shown that the high temperature strength and hardness of Ni 3 Al alloy can be significantly increased by adding Cr 3 C 2 particles, which have the advantages of high hardness, high-temperature stability, excellent high-temperature wear resistance, high compatibility, and wettability with the Ni 3 Al matrix [9][10][11][12]. Fu et al [13] prepared a Cr 3 C 2 /Ni 3 Al composite material using hot isostatic pressing technology, and studied the influence of different chromium carbide contents on the wear resistance of the composite.…”
Section: Introductionmentioning
confidence: 99%